2019
DOI: 10.1001/jamanetworkopen.2019.12902
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Ambient Air Pollution With Thyroid Function During Pregnancy

Abstract: Key PointsQuestionIs exposure to ambient air pollution in the first trimester associated with thyroid function throughout pregnancy?FindingsAmong 9931 pregnant women in 4 European cohorts and 1 US cohort, an increase of 5 μg/m3 in exposure to particulate matter with an aerodynamic diameter of 2.5 μm or less was associated with 20% higher odds of hypothyroxinemia.MeaningThe findings of this study raise the possibility that exposure to particulate matter might disrupt thyroid function in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 48 publications
11
43
0
3
Order By: Relevance
“…In this respect, in iodine de cient mothers, the thyroid gland shifts its secretion from T4 to T3 to maintain iodine; consequently, IMH is more prevalent in iodine de ciency (9,31). However, other novel factors, including exposure with environmental pollutants which may activate the hepatic glucuronidation, competitive inhibition of sodium iodine symporter and binding to the nuclear thyroid hormone receptor (32)(33)(34)(35), obesity leading to increased peripheral deiodination (36)(37)(38)(39)(40), iron de ciency due to reduced activity of the heme-dependent thyroid (41)(42)(43)(44), peroxidase antibodies (21) and pro/antiangiogenic factors (45) are associated with increased risk of IMH.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, in iodine de cient mothers, the thyroid gland shifts its secretion from T4 to T3 to maintain iodine; consequently, IMH is more prevalent in iodine de ciency (9,31). However, other novel factors, including exposure with environmental pollutants which may activate the hepatic glucuronidation, competitive inhibition of sodium iodine symporter and binding to the nuclear thyroid hormone receptor (32)(33)(34)(35), obesity leading to increased peripheral deiodination (36)(37)(38)(39)(40), iron de ciency due to reduced activity of the heme-dependent thyroid (41)(42)(43)(44), peroxidase antibodies (21) and pro/antiangiogenic factors (45) are associated with increased risk of IMH.…”
Section: Discussionmentioning
confidence: 99%
“…The offspring of pregnant women that have been exposed to air pollutants show structural brain alterations, reduced executive function and behavioral problems. The tentative mechanisms for these problems may be oxidative stress, neuroinflammation or changes in the hypothalamic-pituitary-adrenal axis [1]. Thyroid hormones are crucial in the development of the fetal brain.…”
Section: Introductionmentioning
confidence: 99%
“…The fetal thyroid gland is fully functional after mid-pregnancy, thus undiagnosed or less than optimally treated thyroid insufficiency early on in pregnancy adversely affects the development the offspring. Studies have shown a link between pollutants (polycyclic aromatic hydrocarbons) and maternal thyroid function [1]. Particulate air pollutants are prevalent and harmful to humans (as assessed versus mortality, morbidity or cardiovascular disease) [2]; however, data on whether exposure to particulate air pollutants can also disrupt thyroid function in pregnancy are limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations